House Ponders Aid to Maritime School - Vallejo Times-Herald (Vallejo Times-Herald)
The House of Representatives Committee on Merchant Marine and Fisheries took testimony in Washington, D. C., this week on a plan to spend Federal money as an aid to the California Maritime Academy here.